Problematics of The Influence of Islamic Law on The Order of Life of The Badui Community - Pasaribu, Merry Roseline; Rizki, Rizki (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The Badui tribe is one of the tribes in Indonesia that has been able to maintain its customs until now and is a society that has closed itself off to a life that is completely advanced both in terms of technology and science. This research is a sociological juridical research by conducting field research and data collection was carried out using method of observation and interviews from the Badui Dalam and Badui Luar tribal communities. From the research results, it is clear that the inner Badui tribe maintains its customs and beautiful natural environment without being touched by outsiders, although this community does not close itself off from the influx of domestic tourists, but they have a strong order and obey the punun and impose punishments. It is clear that if one of the members of the Badui community violates customary rules by expelling a member of the family, he is not allowed to live in the Badui community anymore. The Badui community does not know what education is, so the children of the Badui tribe do not have formal education in school because it is prohibited, education can make a person dishonest, a fraud, a liar, nepotism and collusion which results in an atmosphere of preserving peace and binding customary harmony. However, the Badui children cannot write but can read, and now some are even able to speak Indonesian. Marriage is monogamous, there is no term for divorce and each couple is matched by both parents and the heirs are male and female children with equal portions. If there are adopted children, their position is the same as biological children, both in terms of inheritance, there is no influence of Islamic law. in the order of life of the inner Badui tribe.